Today’s Research, Tomorrow’s Practice – White Paper from the Translation of New Therapy (TNT) Radiotheranostics Kick-off Pre-meeting of the Annual World Molecular Imaging Conference 2024 - Krebs, Simone; Baird, Lisa; Pirovano, Giacomo; Yamaguchi, Aiko; Coll, Ryan P.; Lee, Jason T.; Carroll, Laurence S.; Pomper, Martin G.; Manning, H. Charles (Molecular imaging and biology, 2025)
Theranostics, a concept combining "therapy" and "diagnostics", is poised to enter an exponential growth phase. By using specific diagnostic markers to guide the selection and application of targeted treatments directed at those markers, this approach aims to improve effectiveness and reduce unnecessary interventions. While several agents have been approved by the FDA recently, multiple additional theranostics are being developed, studied in clinical trials and expected to enter clinical practice in short order. As part of the "Translation of New Therapy (TNT) Interest Group's Radiotheranostics Kick-off" pre-meeting of the annual World Molecular Imaging Conference (WMIC) 2024 over 350 attendees with 10% leaders from industry, 60% senior and junior investigators in academia and 30% trainees discussed the key challenges and opportunities in implementing a theranostic research program in academia, which are addressed in this white paper. Overarching themes included funding, regulatory hurdles, and workforce training. Panel recommendations included leveraging existing expertise and patient populations, securing revenue streams, exploring alternative funding sources, and developing a multifaceted approach to promote training, education and public awareness, including fostering academic-industry partnerships. By shedding light on the gap between research and real-world program implementation, this white paper and forthcoming pre-meetings at WMIC aim to define a practical framework for building successful programs based on insights from recent research.